Neuromuscular Electrical Stimulation of Abdominal Muscles to Improve Standing Balance - Jeongwoo Je; Woochol Joseph Choi (Korean Research Society of Physical Therapy, 2022)
Background: Neuromuscular electrical stimulation (NMES) is used for muscle strengthening. While voluntary muscle contraction follows Henneman et al.'s size principle, the NMES-in-duced muscle training disrespects the neurophysiology, which may lead to unwanted changes (i.e., declined balance ability).Objects: We examined how the balance was affected by abdominal muscle training with the NMES.Methods: Fifteen young adults (10 males and 5 females) aged between 21 and 30 received abdominal muscle strengthening with NMES for 23 minutes. Before and after the training, participants' balance was measured through one leg standing on a force plate with eyes open or closed. Outcome variables included mean distance (MDIST), root mean square dis-tance (RDIST), total excursion (TOTEX), mean velocity (MVELO), and 95% confidence circle area (AREA) of center of pressure data. Two-way repeated measures analysis of variance was used to test if these outcome variables were associated with time (pre and post) and vision.Results: All outcome variables were not associated with time (p > 0.05). However, all out-come variables were associated with vision (p = 0.0001), and MVELO and TOTEX were 52.4% (45.5 mm/s versus 95.6 mm/s) and 52.4% (364.1 mm versus 764.5 mm) smaller, respectively, in eyes open than eyes closed (F = 55.8, p = 0.0005; F = 55.8, p = 0.0005). Furthermore, there was no interaction between time and vision (F = 0.024, p = 0.877).Conclusion: Despite the different neurophysiology of muscle contraction, abdominal muscle strengthening with NMES did not affect balance.